2001
DOI: 10.1103/physrevd.63.064024
|View full text |Cite
|
Sign up to set email alerts
|

Constant crunch coordinates for black hole simulations

Abstract: We reinvestigate the utility of time-independent constant mean curvature foliations for the numerical simulation of a single spherically-symmetric black hole. Each spacelike hypersurface of such a foliation is endowed with the same constant value of the trace of the extrinsic curvature tensor, K. Of the three families of K-constant surfaces possible (classified according to their asymptotic behaviors), we single out a sub-family of singularity-avoiding surfaces that may be particularly useful, and provide an a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…Moncrief presented the first explicit construction of a hyperboloidal scri-fixing gauge for Minkowski spacetime [72] (for numerical implementations see [73][74][75]). The application of the method in black-hole spacetimes proved to be difficult [76][77][78][79][80], until the general construction of suitable hyperboloidal scri-fixing coordinates on asymptotically flat spacetimes has been presented [81]. Since then, hyperboloidal scri-fixing coordinates have been employed in a rich variety of problems concerning black-hole spacetimes [22,[82][83][84][85][86][87][88][89][90][91].…”
Section: Introductionmentioning
confidence: 99%
“…Moncrief presented the first explicit construction of a hyperboloidal scri-fixing gauge for Minkowski spacetime [72] (for numerical implementations see [73][74][75]). The application of the method in black-hole spacetimes proved to be difficult [76][77][78][79][80], until the general construction of suitable hyperboloidal scri-fixing coordinates on asymptotically flat spacetimes has been presented [81]. Since then, hyperboloidal scri-fixing coordinates have been employed in a rich variety of problems concerning black-hole spacetimes [22,[82][83][84][85][86][87][88][89][90][91].…”
Section: Introductionmentioning
confidence: 99%
“…For more generic, multiple black hole situations, it should be possible to construct shift vectors that preserve this property. If not, a large enough value of n should be able to yield the appropriate sign of C. Finally, we point out that this hand-waving argument provides a reasonable explanation of why the simulations in [8] with K = const < 0 were significantly more stable than those with positive K.…”
Section: T F Ijmentioning
confidence: 57%
“…Their hyperboloidal foliation is based on a scri-fixing gauge in Minkowski spacetime first explicitly constructed by Moncrief [79] (see also [76]). It was suggested that scri-fixing gauges should be beneficial also for studies on black-hole spacetimes, however, the construction of a good hyperboloidal coordinates turned out to be difficult [80][81][82][83][84][85].…”
Section: A Hyperboloidal Compactificationmentioning
confidence: 99%